Specification for harmonized system of quality assessment for electronic components. Fixed capacitors for use in electronic equipment. Blank detail specification: fixed tantalum capacitors with non-solid electrolyte and foil electrode. Assessment level E. (15th April 1985) - British Standards Institution,
No abstract available